Peran Manajemen Risiko Keuangan dalam Meminimalkan Potensi Kebangkrutan pada Perusahaan - A, Afriani; Sari, Yuni Fatma; Dewi Zai, Siti Hansyah; Pasaribu, Fanny Himla Rizqya; A, Arsyadona (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Bankruptcy is one of the main tests faced by companies in an increasingly competitive and changeable business environment. This research aims to analyze how financial risk management can reduce the likelihood of bankruptcy. Using a qualitative approach, the study explores various techniques and strategies of risk management implemented by companies to identify, analyze, and address financial risks. The results indicate that effective risk management practices, including portfolio diversification, cash flow analysis, and the use of derivative instruments, can significantly reduce the risk of bankruptcy. Additionally, an organizational culture that supports risk management plays a crucial role in enhancing a company's resilience amid market uncertainties. This research recommends that company managers integrate financial risk management into their overall business strategy to ensure operational sustainability and prevent bankruptcy.